Piercing the veil on the functioning and effectiveness of district health system governance structures: perspectives from a South African province - Khanyisile Tshabalala; Laetitia C. Rispel (BMC, 2023)
Abstract Background Leadership and governance are critical for achieving universal health coverage (UHC). In South Africa, aspirations for UHC are expressed through the proposed National Health Insurance (NHI) system, which underscores the importance of primary health care, delivered through the district health system (DHS). Consequently, the aim of this study was to determine the existence of legislated District Health Councils (DHCs) in Gauteng Province (GP), and the perceptions of council members on the functioning and effectiveness of these structures. Methods This was a mixed-methods, cross-sectional study in GP's five districts. The population of interest was members of existing governance structures who completed an electronic-self-administered questionnaire (SAQ). Using a seven-point Likert scale, the SAQ focuses on members' perceptions on the functioning and effectiveness of the governance structures. In-depth interviews with the chairpersons of the DHCs and its technical committees complemented the survey. STATA® 13 and thematic analysis were used to analyze the survey data and interviews respectively. Results Only three districts had constituted DHCs. The survey response rate was 73%. The mean score for perceived functioning of the structures was 4.5 (SD = 0.7) and 4.8. (SD = 0.7) for perceived effectiveness. The interviews found that a collaborative district health development approach facilitated governance. In contrast, fraught inter-governmental relations fueled by the complexity of governing across two spheres of government, political differences, and contestations over limited resources constrained DHS governance. Both the survey and interviews identified gaps in accountability to communities. Conclusion In light of South Africa's move toward NHI, strengthening DHS governance is imperative. The governance gaps identified need to be addressed to ensure support for the implementation of UHC reforms.